Використання методів обробки зображень для оптимізації 3D-моделей у комп’ютерних іграх - Ніколаєв, І. Д. (ХНУРЕ, 2025)
The article discusses the main methods of optimizing 3D models for computer games, ensuring a balance between image quality and performance. Particular attention is paid to the techniques of levels of detail (LOD), normal maps and texture compression methods. The use of these approaches allows to reduce the load on hardware resources, improving the performance of the game engine. Also, modern algorithms and tools used in popular game engines, such as Unity and Unreal Engine, are considered.
Keywords: обробка зображень; оптимізація 3D-моделей